ШЫМБАЙ ТОПОНИМЛЕРИ – ХАЛЫҚ ҚОСЫҚЛАРЫНДА - Абишов, Г.М.; Махсетова, Ж. (SCIENCE and SOCIETY, 2018)
The appearance of toponyms and their change are closely connected with the history of people. Geographical items appeared on the basis of events and phenomena which appeared in the nation’s life as essential (natural) symbols of geographical objects. Every epoch leaves its footprint in the appearance of toponyms. In the article the toponyms of Chimbai were investigated on the examples of folk poems. The definitions of toponyms used in love poems, comic and vital poems are given. Their geographical location in the region is shown.